1996
DOI: 10.3354/meps135137
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular storage of mercury and selenium in different marine vertebrates

Abstract: Intracellular storage and levels of mercury and selenium were studied in the livers of top marine predators belong~ng to different vertebrate taxa. Total mercury levels showed very important interspecific variations, ranging from 2.6 pg g.' In tuna and swordfish to several thousand pg g-' (dry weight) in bottle-nosed and Risso's dolphins. However, methylmercury was less variable, ranging from 1 to 174 pg g.' (dry weight). The ratio between Hg and Se levels was close to equimolarity in marine mammals and cormor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
100
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(112 citation statements)
references
References 21 publications
11
100
1
Order By: Relevance
“…Except for B. physalus and P. macrocephalus, the molar ratio between inorganic mercury and selenium is nearly 1 in the liver of adult individuals (mean value 0.8), in agreement with the observations of several authors (Monaci et al, 1998;Cardellicchio et al, 2000). This confirms the existence of a fact that there is a bio-transformation process in which methylmercury is converted into the less toxic inorganic form (Thibaud, 1986), with subsequent formation of granules of mercury selenide (Nigro and Leonzio, 1996). As evident in Fig.…”
Section: Mercurysupporting
confidence: 78%
See 1 more Smart Citation
“…Except for B. physalus and P. macrocephalus, the molar ratio between inorganic mercury and selenium is nearly 1 in the liver of adult individuals (mean value 0.8), in agreement with the observations of several authors (Monaci et al, 1998;Cardellicchio et al, 2000). This confirms the existence of a fact that there is a bio-transformation process in which methylmercury is converted into the less toxic inorganic form (Thibaud, 1986), with subsequent formation of granules of mercury selenide (Nigro and Leonzio, 1996). As evident in Fig.…”
Section: Mercurysupporting
confidence: 78%
“…The case of Se is peculiar. It is an essential element, yet it is subjected to large variations related to high Hg levels (Thibaud, 1986;Nigro and Leonzio, 1996). As the number of specimens available in this kind of studies is often small, the comparison with literature data is useful and necessary.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a Kupffer cell (macrophages) could be recognized by its ultrastructure and presented electro-dense granules within the lysosomes which would correspond to intracellular deposits of Hg\ \Se (Fig 3B). Although some studies found mercury deposits in hepatocytes of bottlenose dolphins (Tursiops truncatus, Rawson et al, 1993) and pilot whales (Globicephala melas, Stoltenberg et al, 2003), the primary cell involved in storage of HgSe is suggested to be the Kupffer cell (Nigro, 1994;Nigro and Leonzio, 1996;Lailson-Brito et al, 2012). Our results support this role of macrophages in the detoxification process of Hg in liver.…”
supporting
confidence: 79%
“…Mercury selenides have been detected using electron microscopy as forming spherical concretions which aggregate to form granules or calculi of variable sizes in the livers of T. truncatus (Martoja & Viale 1977;Nigro & Leonzio 1996) and Grampus griseus (Nigro & Leonzio 1996). Relatively high concentrations of Hg were found in the analysed kidney samples in both species.…”
Section: Bioaccumulation Of Mercury In Tissues Of Analysed Speciesmentioning
confidence: 99%